Transcriptional regulators in hepatocarcinogenesis: key integrators of malignant transformation - Malz, Mona; Pinna, Federico; Schirmacher, Peter; Breuhahn, Kai (Journal of hepatology, 2012)
Summary Hepatocellular carcinoma (HCC) is one of the most frequent human malignancies with poor prognosis and increasing incidence in the Western world. Only for a minority of HCC patients, surgical treatment options offer potential cure and therapeutic success of pharmacological approaches is limited. Highly specific approaches (e.g., kinase inhibitors) did not significantly improve the situation so far, possibly due to functional compensation, genetic heterogeneity of HCC, and development of resistance under selective pressure. In contrast, transcriptional regulators (especially transcription factors and co-factors) may integrate and process input signals of different (oncogenic) pathways and therefore represent cellular bottlenecks that regulate tumor cell biology. In this review, we want to summarize the current knowledge about central transcriptional regulators in human hepatocarcinogenesis and their potential as therapeutic target structures. Genomic and transcriptomic data of primary human HCC revealed that many of these factors showed up in subgroups of HCCs with a more aggressive phenotype, suggesting that aberrant activity of transcriptional regulators collect input information to promote tumor initiation and progression. Therefore, expression and dysfunction of transcription factors and co-factors may gain relevance for diagnostics and therapy of HCC.